2013
DOI: 10.1089/ten.tea.2012.0407
|View full text |Cite
|
Sign up to set email alerts
|

Cord Lining-Mesenchymal Stem Cells Graft Supplemented with an Omental Flap Induces Myocardial Revascularization and Ameliorates Cardiac Dysfunction in a Rat Model of Chronic Ischemic Heart Failure

Abstract: Myocardial restoration using tissue-engineered grafts to regenerate the ischemic myocardium offers improved donor cell retention, yet a limited cell survival resulting from poor vascularization needs to be addressed. A cell type derived from the subamnion, namely, cord-lining mesenchymal stem cells (CL-MSC), has recently been identified. Here we present a restorative strategy that combines a fibrin graft containing human CL-MSC and omental flap providing, thereby, cell-, structural-, and angiogenic support to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
0
21
1
Order By: Relevance
“…Yet, the possibility that differentiation might have occurred by cell fusion could not be excluded. These findings differ from our previous study, as we were not able to detect CL-MSC-derived vascular differentiation in the few engrafted cells found 1 month after implantation of monodispersed CL-MSC seeded within FGs in failing rat hearts [14]. Thus, self-assembly of CL-MSC into 3D spheroids might have favored vascular differentiation.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Yet, the possibility that differentiation might have occurred by cell fusion could not be excluded. These findings differ from our previous study, as we were not able to detect CL-MSC-derived vascular differentiation in the few engrafted cells found 1 month after implantation of monodispersed CL-MSC seeded within FGs in failing rat hearts [14]. Thus, self-assembly of CL-MSC into 3D spheroids might have favored vascular differentiation.…”
contrasting
confidence: 99%
“…We have recently shown that monodispersed CL-MSC embedded within FGs prevented further deterioration of cardiac function in failing rat hearts. Yet, the combination of CL-MSC grafts with a vascular omental flap had a synergistic effect that promoted myocardial revascularization improving thereby cardiac function and adverse remodeling [14]. In the present study, CL-MSC were used to assemble angiogenic spheroids that were then coated with HUVEC.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Their results showed a general recovery of lost cardiac functions. Further studies in rat MI models have applied fibrin‐based scaffolds loaded with ESC‐derived cardiac progenitors (Menasché et al , ; Bellamy et al , ), neonatal rat cardiac cells (Wendel et al , ), MSCs from the subamnion (Lilyanna et al , ) or skeletal myoblasts (Christman et al , ). All those strategies provided sustained improvements in myocardial vessel density and cardiac function, and they attenuated post‐MI remodelling.…”
Section: Fibrin‐based Scaffolds For Cardiac Tissue Engineeringmentioning
confidence: 99%
“…Several experimental studies showed the benefits of engineered materials charged with stem cells for ischemic models. In addition, in some of these studies the cell transplantation was associated with epicardial grafting of scaffolds onto the ventricular surface [11][12][13][14]. Subsequently, our group coordinated the MAGNUM Clinical Trial (Myocardial Assistance by Grafting a New bioartificial Upgraded Myocardium).…”
Section: Myocardial Tissue Engineeringmentioning
confidence: 99%